2007
DOI: 10.1021/jf062887+
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Biogenic Amines in Squid and White Prawn by High-Performance Liquid Chromatography with Postcolumn Derivatization

Abstract: A simple method was developed for the determination of biogenic amines in aquatic food products using a reverse-phase high-performance liquid chromatography with postcolumn automatic o-phthalaldehyde derivatization and fluorescence detection. The linearity, repeatability, and recovery of the method for seven amines (tyramine, putrescine, cadaverine, histamine, agmatine, spermidine, and spermine) were evaluated. This optimized method was applied to detect biogenic amines in squid and white prawn during refriger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
2
10
2
Order By: Relevance
“…The amounts of agmatine and cadaverine in the control samples increased to 17.45 and 4.43 mg/kg, respectively, after 28 d of storage, while the dopamine content significantly decreased from 3.44 to 1.04 mg/kg. This is in good agreement with the results from Zhao and others (2007), who reported that the amounts of agmatine and cadaverine in squid significantly increased with increasing storage time at both 0 and 4 °C. When compared to other BAs, the agmatine content was dominant in the semidried squid samples, which is more likely due to the abundance of endogenous arginine.…”
Section: Resultssupporting
confidence: 93%
“…The amounts of agmatine and cadaverine in the control samples increased to 17.45 and 4.43 mg/kg, respectively, after 28 d of storage, while the dopamine content significantly decreased from 3.44 to 1.04 mg/kg. This is in good agreement with the results from Zhao and others (2007), who reported that the amounts of agmatine and cadaverine in squid significantly increased with increasing storage time at both 0 and 4 °C. When compared to other BAs, the agmatine content was dominant in the semidried squid samples, which is more likely due to the abundance of endogenous arginine.…”
Section: Resultssupporting
confidence: 93%
“…Benner et al (6) have suggested putrescine as the best indicator of decomposition for penaeid shrimp stored at a wide range of temperatures (0 °C to 36 °C) and proposed the putrescine level of 3 mg kg -1 as a threshold for human consumption. In contrast to our study, increase in putrescine was accompanied by increase in cadaverine in decomposed pink shrimp (Litopenaeus brasiliensis) (6), Indian shrimp (Parapenaeopis stylifera) (24), and white prawn (25).…”
Section: Biogenic Amines In Norway Lobstercontrasting
confidence: 99%
“…Finally, putrescine, tyramine and spermidine exhibited positive correlation relationship with histamine forming bacteria ( r 2 = .938, .965, .952, respectively, p < .05). In agreement to the results obtained in this study, Zhao et al () reported the accumulation of tyramine, putrescine, cadaverine, histamine, and agmatine during storage of L. vannamei at 0 and 4 °C for 8 days. Benner et al () reported the accumulation of putrescine and cadaverine during storage of L. setiferus at 0 and 12 °C for 16 and 4 days, respectively, as well as L. brasiliensis at 24 and 36 °C for 48 and 24 hr, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Then, an increase was observed until the 15 th day of storage that reached 5.6 mg/100 g muscle. Similarly, Zhao et al () reported that histamine was not detected in L. vannamei during the first 2 days of storage at 0 and 4 °C but reached 0.48 and 0.68 mg/Kg, respectively after 8 days of storage. However, this amount is much less than he change to the respective reported for several fish species.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation